HCI in Business, Government and Organizations: 8th International Conference, HCIBGO 2021, Virtual Event, July 24-29: Proceedings - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2020)
This book constitutes the refereed proceedings of the 8th International Conference on HCI in Business, Government and Organizations, HCIBGO 2021, which was held as part of HCI International 2021 and took place virtually during July 24-29, 2021. The total of 1276 papers and 241 posters included in the 39 HCII 2021 proceedings volumes was carefully reviewed and selected from 5222 submissions. The papers included in this book were organized in topical sections as follows: electronic, mobile and ubiquitous commerce; HCI in finance and industry; work and business operations; innovation, collaboration, and knowledge sharing; and digital transformation and artificial intelligence.